ANALISIS KONTEN BUKU AL-AL’AB AL-LUGHAWIYAH LI ATHFAL QABLAL MADRASAH DALAM PENGEMBANGAN KETERAMPILAN BERBAHASA ARAB ANAK USIA DINI - Muhammad Zaairul Haq (STAINU Purworejo, 2023)
Abstract This research aims to investigate the role and benefits of language games in early childhood education. Language games have the potential to strengthen language skills and facilitate children's learning in a fun and interactive context. The research was conducted using a qualitative method through content analysis of the book